Evaluation of methylparaben removal and microbial behavior using a SBR system (2019)
ABSTRACT : We evaluated the variation in microbial populations and the behavior of an SBR system in the removal of methylparaben (MePB). The experimentation was carried out for 14 weeks, in three operational stages as follows: stabilization (Stage I), (Stage II = 300 µgMePB/L and Stage III = 600 µgMePB/L). The variation of the microorganisms was analyzed over the experimentation time along with the contact with the pollutant to be degraded, and the removal percentage of COD and MePB, with results of 88 ± 5,5% and 92 ± 7,7% respectively. Kinetic of MePB removal was evaluated to obtain the rate constant of biological degradation, Kbiol. Using these kinetic results, the effect of different concentrations of MePB and biomass on biodegradation behavior was evaluated. Kbiol (LgSS-1d -1) values were obtained of 42.8 and 79 respectively; and 472 ± 38.0 µgMePB/L, at biomass contents of 1466.7 and 2666.7 mgSSV/L, where Kbiol (LgSS-1d -1) values were obtained of 11.0 and 32.6 respectively. The variation of the microbial populations were analyzed using DGGE. The results obtained indicated that the populations presented similar characteristics between the stages. However, for the biomass samples of Stage I and stage III, significant differences were identified in the composition of microbial populations. Nonetheless, this did not affect the removal of MePB and the diversity conditions that characterize an aerobic system.